Exploring Junior High School Students on Self-Collection Strategy in Learning Vocabulary; Classroom Action Research - Rasmini, Maharani; Al-Baekani, Abdul Kodir; Kamil, Acep Bahrun (Jurnal Ilmiah Wahana Pendidikan, 2024)
One of the main aspects in language acquisition is vocabulary. A good vocabulary allows students to understand, communicate and express themselves better. Therefore, the researcher aims to discover students' experiences while using the VSS strategy with the help of interactive film media. Researchers used a qualitative research approach with a classroom action research design. Research participants were junior high school students at one of the Karawang schools. Research data was obtained from observations and interviews with research participants. The research results show that the emphasis on affective and behavioral aspects of students learning English with the VSS strategy tends to be more dominant. Most research participants felt happy and motivated in learning. This triggers students to behave positively in class by paying attention to the teacher and actively discussing in class or groups. This research concludes that students' affective aspects can trigger student behavior in the classroom. Therefore, teachers need to have the ability to master engaging, active and interactive teaching, so that this can help students to achieve learning goals. The results of this research can provide objective evidence of students' experiences using the VSS strategy by utilizing film media in language learning.